Pengaruh Audit Operasional Dan Motivasi Kerja Terhadap Efektivitas Pelayanan Kesehatan Dirumah Sakit Mujaisyah - Tenri Andi Nur; Rismawati Rismawati; Andika Rusli (Politeknik Ganesha Medan, 2023)
The purpose of this study was to analyze the effect of operational auditing and work motivation on the effectiveness of hospital health services. This study uses a quantitative approach, using primary data through distributing questionnaires. The sample of this research is the employee of Mujaisyah Hospital, Palopo City. Two variables in this study, namely operational audit and work motivation as independent variables, and the effectiveness of health services in hospitals as the dependent variable. The analytical method used in this study is multiple linear regression analysis and the data analysis tool used in this study is Statistical Products and Services Solutions (SPSS) type 26 for windows. The results of this study can prove that operational audit has a positive effect on the effectiveness of health services in hospitals with a sig value of 0.009 <0.05, so it can be concluded that H1 is accepted. In addition, this study also proves that work motivation has a positive effect on the effectiveness of health services in hospitals with a sig value of 0.006 <0.05 so it can be concluded that H2 is also accepted. The two independent variables above have a positive effect on the dependent variable.